Estimating the quantity of consumed plastic products and their economic returns in the city of Benghazi1 - Elsheikhi, Salah; Mohamed, Hamzah; Eldressi, Khaled (Libyan Journal of Science &Technology, 2022)
Abstract Plastics recycling has gained significance and popularity over the last few decades due to environmental and economic reasons. Huge quantities of plastic products can be found in Benghazi city in places such as hospitals, restaurants, schools, factories, etc. Rather than accumulating these plastics products in the landfill areas, they can be recycled. Such an action preserves the environment and leads to great financial savings. This study aims to gather data on post-consumer plastic products from different locations and facilities in Benghazi. The plastics products have been classified into five types namely, PET, HDPE, LDPE, PP, and PS. The results revealed that many of the consumed products were PET. The study also reported the potential economic return of these products to some public institutions such as schools, the orphanage, and the homes of the disabled. Also, the study may serve as a starting point to the municipality of Benghazi and other local authorities towards improving the utilization of plastics waste and realizing the significance of their economic return.